2015
DOI: 10.1021/cs501668g
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Hägg Iron-Carbide-Catalyzed Fischer–Tropsch Synthesis: Suppression of CH4 Formation and Enhancement of C–C Coupling on χ-Fe5C2 (510)

Abstract: Probing the product selectivity of Fischer–Tropsch catalysts is of prime scientific and industrial importancewith the aim to upgrade products and meet various end-use applications. In this work, the mechanisms for CH4 formation and C1–C1 coupling on a thermodynamically stable, terraced-like χ-Fe5C2 (510) surface were studied by DFT calculations. It was found that this surface exhibits high effective barriers of CH4 formation for the three cases (i.e., 3.66, 2.81, and 2.39 eV), indicating the unfavorable occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
114
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 47 publications
5
114
0
1
Order By: Relevance
“…In addition, the findings by Pallassana and Neurock on C 2 H 4 hydrogenation suggest that the C−H bond activation of ethyl and ethylene is primarily guided by electron‐back donation to the antibonding σCH* orbital, the catalytic activity of C−H bond formation increases on Pd catalyst surfaces where the d‐band is far from the Fermi level. These also agree with the previous studies about CH x hydrogenation to CH 4 …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the findings by Pallassana and Neurock on C 2 H 4 hydrogenation suggest that the C−H bond activation of ethyl and ethylene is primarily guided by electron‐back donation to the antibonding σCH* orbital, the catalytic activity of C−H bond formation increases on Pd catalyst surfaces where the d‐band is far from the Fermi level. These also agree with the previous studies about CH x hydrogenation to CH 4 …”
Section: Resultssupporting
confidence: 93%
“…These also agree with the previous studies about CH x hydrogenation to CH 4 . [65][66][67] The above resultss how that over Pd-doped Cu(111)s urfaces, the higher the selectivity towards C 2 H 4 formation is, the lower the activity towards C 2 H 4 formation is.M oreover,c ompared with Cu(111), both Pd 1 Cu 8 and Pd 3 Cu 6 surfaces with only surface single-atom Pd monomer sites presentahigh selectivity and ar elatively low activity in C 2 H 4 formation,whereas Pd 6 Cu 3 ,P d 9 Cu 0 ,a nd Pd(111)s urfaces exhibit al ow selectivity and ar elatively high activity owing to the existence of surface Pd dimer and trimer sites. These results also mean that the Pd-Cu-Cu trimer ensemble over Pd 1 Cu 8 and Pd 3 Cu 6 surfaces is of benefitf or the selectivityt owardC 2 H 4 formation,a nd the Pd-Cu dimer ensemblei so fb enefit for the activity of C 2 H 4 formation.…”
Section: The Activity Of C 2 H 4 Formationmentioning
confidence: 64%
“…However, it may also be significant that Ru,Fe@NCNT appear to stabilize iron carbides and lower oxidation states of iron, a trend that is agreement with XPS analysis (Figure ), as the Hägg carbide (cementite) is known to be the active phase in iron‐drive FT catalysis . A catalyst that stabilizes more reduced forms of iron and allows for more facile formation of the Hägg carbide during catalysis would be expected to have high activity in the FT reaction and good capability for chain lengthening to higher hydrocarbon products; a trend that is observed in the product distribution of Ru,Fe@NCNT versus Ru−Fe@NCNT (Figure ).…”
Section: Resultssupporting
confidence: 54%
“…[35] Consequently,e thylene hydrogenation was conducted to compare the hydrogenation ability of alkenes on in situ prepared c-Fe 5 C 2 and q-Fe 3 C. Ap eak area ratio of ethane ( Figure S14) for c-Fe 5 C 2 is weaker than that for q-Fe 3 C (peak area ratio of c-Fe 5 C 2 to q-Fe 3 Ci s2 5:60), which demonstrates the weaker hydrogenationa bility for c-Fe 5 C 2 .I na ddition, Pham et al [36] calculated the effective barrier (DE eff )o fC 1 -C 1 coupling over c-Fe 5 C 2 and found that higher DE eff represented lower selectivity to long-chain hydrocarbons.E mit et al [26] found that the c-Fe 5 C 2 surface exhibited ah igher DE eff than q-Fe 3 C. Furthermore, CO 2 -TPD profiles ( Figure S15) indicate that q-Fe 3 Cs hows as tronger CO 2 adsorption capability and greater chain growth probability than c-Fe 5 C 2 .F or these reasons, c-Fe 5 C 2 may suppress the secondary hydrogenation of alkenes and accelerates alkened esorption, which lead to ah igh selectivity to short-chain alkenes;w hile q-Fe 3 Cs hows ah igher C 5 + In summary,u sing operando techniques complemented with well-designed experiments,t he structure evolution and structure-performance relationship of iron-based catalysts during CTH have been elaborated by conducting as ystematically comparative study for a-Fe 2 O 3 and g-Fe 2 O 3 .S pecifically, we have demonstrated that the generation of c-Fe 5 C 2 and q-Fe 3 Cf rom a-Fe 2 O 3 and g-Fe 2 O 3 ,r espectively,s houldb er esponsible for the performance deviation for two catalysts.F urthermore, experiments show that the highers electivity to lower olefins on c-Fe 5 C 2 is due to its highere ffective barrier,b ut weaker alkenes hydrogenationa bility.T he high selectivity to C 5 + hydrocarbonso nq-Fe 3 Ci sm ainly attributed to its strong CO 2 adsorption, which can enhancet he chain-growtho fa dsorbedc arbonaceous species. [35] Consequently,e thylene hydrogenation was conducted to compare the hydrogenation ability of alkenes on in situ prepared c-Fe 5 C 2 and q-Fe 3 C. Ap eak area ratio of ethane ( Figure S14) for c-Fe 5 C 2 is weaker than that for q-Fe 3 C (peak area ratio of c-Fe 5 C 2 to q-Fe 3 Ci s2 5:60), which demonstrates the weaker hydrogenationa bility for c-Fe 5 C 2 .I na ddition, Pham et al [36] calculated the effective barrier (DE eff )o fC 1 -C 1 coupling over c-Fe 5 C 2 and found that higher DE eff represented lower selectivity to long-chain hydrocarbons.E mit et al [26] found that the c-Fe 5 C 2 surface exhibited ah igher DE eff than q-Fe 3 C. Furthermore, CO 2 -TPD profiles ( Figure S15) indicate that q-Fe 3 Cs hows as tronger CO 2 adsorption capability and greater chain growth probability than c-Fe 5 C 2 .F or these reasons, c-Fe 5 C 2 may suppress the secondary hydrogenation of alkenes and accelerates alkened esorption, which lead to ah igh selectivity to short-chain alkenes;w hile q-Fe 3 Cs hows ah igher C 5 + In summary,u sing operando techniques complemented with well-designed experiments,t he structure evolution and structure-performance relationship of iron-based catalysts during CTH have been elaborated by conducting as ystematically comparative study for a-Fe 2 O 3 and g-Fe 2 O 3 .S pecifically, we have demonstrated that the generation of c-Fe 5 C 2 and q-Fe 3 Cf rom a-Fe 2 O 3 and g-Fe 2 O 3 ,r espectively,s houldb er esponsible for the performance deviation for two...…”
mentioning
confidence: 88%